Sovereign Wealth Funds: Size, economic effects and policy reactions - Thomas Jost (Hochschule für angewandte Wissenschaften Amberg-Weiden (HAW), 2009)
The emergence of Sovereign Wealth Funds (SWFs) and some spectacular investments of these funds in recent years have caused widespread attention on international financial markets. Most SWFs are domiciled in Arabian countries, East Asia and Russia. Their low transparency led to concerns that SWFs could threat national security and the economic order of industrialised countries. This paper describes the growth and the investment strategy of SWFs, the impact of their investments on host and investing countries as well as policy reactions of selected countries. Several international organisations (European Union, OECD, the IMF together with the International Working Group of Sovereign Funds) have already undertaken initiatives that will help to improve the transparency and accountability of SWFs and to develop best practices for investing countries as well as for recipient countries. National policy reactions of several host countries, like the tightening of rules for cross-border investments in the United States and in Germany, were therefore rather counterproductive. – – Das Wachstum und eine Reihe von spektakulären Investitionen von Sovereign Wealth Funds (SWFs) haben in den letzten beiden Jahren auf den internationalen Finanzmärkten für viel Aufsehen gesorgt. Aufgrund der geringen Transparenz vieler SWFs gab es Befürchtungen, dass diese Fonds, die überwiegend in arabischen Ländern, Ostasien und Russland angesiedelt sind, eine Bedrohung für die nationale Sicherheit und das Wirtschaftssystem von Industriestaaten sein könnten. In dem vorliegenden Beitrag werden das Wachstum und die Anlagestrategie von SWFs, die Auswirkungen ihrer Investitionen auf Empfänger- und Geberländer sowie die Politikmaßnahmen der betroffenen Länder beschrieben. Es zeigt sich, dass die nationalen Reaktionen der Empfängerländer, zum Beispiel die Verschärfung der Regelungen für grenzüberschreitende Investitionen in den Vereinigten Staaten und Deutschland, wahrscheinlich zu weit gingen, zumal auf supranationaler Ebene (Europäische Union, OECD und IWF zusammen mit einer Arbeitsgruppe von SWFs) bereits Initiativen auf den Weg gebracht wurden, die zu einer verantwortungsvollen und transparenteren Politik der SWFs wie auch der Empfängerländer von Investitionen beitragen.
Keywords: G32; G15; G38; 330; Sovereign Wealth Funds; international financial markets; government policy; regulation